Critical Orientalism Approaches in Qur'anic and Tafsir Studies: Tracing Armando Salvatore's Contribution to Arab Culture - Nurhaidah, Siti Nuri; Karim, Abdul; Hidayat, Khairul; Marwan, Andi (Program Studi Ilmu Al-Qur`an dan Tafsir, Fakultas Ushuluddin, UIN Sunan Kudus, 2024)
Traditional Orientalism studies are often seen as neglecting the internal and local contexts of Eastern societies, particularly in the study of the Qur'an and Tafsir. This approach frequently gives rise to biased views and stereotypes about Arab and Islamic culture. This article examines Armando Salvatore's contributions to the development of critical Orientalism, especially in relation to the study of the Qur'an and Tafsir. Critical Orientalism offers a more contextual and inclusive approach, taking into account local social and political dynamics, while also creating space for perspectives from within Eastern societies themselves. This research analyzes Salvatore's major works through an in-depth literature review, focusing on how his critical orientalism approach can be applied to understanding Arab culture and the interpretation of the Quran. The methods used in this study include a critical analysis of Salvatore's texts as well as a comparison with traditional orientalist approaches. This study found that Salvatore successfully challenged biases in conventional Orientalism and emphasized the importance of understanding the Quran and Arab culture through local and contextual perspectives.The implications of this approach in the study of the Quran and Tafsir are very important, as it offers a new way to understand religious texts that is more sensitive to the Arab socio-cultural context. Salvatore's critical orientalism approach not only helps bridge the gap between Western understanding and Eastern realities but also has the potential to enrich Quranic exegesis studies through a more inclusive and dynamic perspective. Kajian orientalisme tradisional seringkali dianggap mengabaikan konteks internal dan lokal masyarakat Timur, terutama dalam studi Al-Qur'an dan Tafsir. Pendekatan ini sering memunculkan pandangan yang bias dan stereotip tentang budaya Arab dan Islam. Artikel ini mengkaji kontribusi Armando Salvatore dalam pengembangan orientalisme kritis, khususnya dalam kaitannya dengan studi Al-Qur'an dan Tafsir. Orientalisme kritis menawarkan pendekatan yang lebih kontekstual dan inklusif, memperhitungkan dinamika sosial dan politik lokal, serta membuka ruang bagi pandangan dari dalam masyarakat Timur sendiri. Penelitian ini menganalisis karya-karya utama Salvatore melalui tinjauan literatur mendalam, dengan fokus pada bagaimana pendekatan orientalisme kritisnya dapat diterapkan dalam memahami budaya Arab dan tafsir Al-Qur'an. Metode yang digunakan dalam penelitian ini mencakup analisis kritis terhadap teks-teks Salvatore serta perbandingan dengan pendekatan orientalis tradisional. Studi ini menemukan bahwa Salvatore berhasil menantang bias-bias dalam orientalisme konvensional dan menggarisbawahi pentingnya memahami Al-Qur'an dan budaya Arab melalui perspektif lokal dan kontekstual. Implikasi dari pendekatan ini dalam studi Al-Qur'an dan Tafsir sangatlah penting, karena menawarkan cara baru untuk memahami teks-teks keagamaan yang lebih peka terhadap konteks sosial-budaya Arab. Pendekatan orientalisme kritis Salvatore tidak hanya membantu menjembatani kesenjangan antara pemahaman Barat dan realitas Timur, tetapi juga berpotensi memperkaya studi tafsir Al-Qur'an melalui perspektif yang lebih inklusif dan dinamis.